Fragmented Democracies, Power Control and Principle of Responsibility. A New Constitutionalism in the Age of Global Market - Jordi Jaria i Manzano (Estudios de Deusto, 2014)
Political power is experiencing a deep reorganisation in last decades, parallel to process of global integration of markets. Nation-state is somehow superseded within this new scenario. That implies new challenges to constitutionalism in order to design updated tools to guarantee the limitation of power and the status of citizens. For this reason it is required to think about a new global constitutional framework, based in fragmentation, pluralism and responsibility. Published online: 27 November 2014